Metodologias de pesquisa utilizadas nos Programas de Pós-Graduação em Ciência da Informação do IBICT e UNESP nos anos de 2014 a 2016 - COSTA, Patrícia Danielle Souza (2018)
It presents a study about the importance of methodological choices for the development of scientific research, as a necessary tool to make the research process more organized, dynamic and efficient. The objective of this work is to identify the methodological choices in the theses defended in the postgraduate programs in Information Science of the IBICT and UNESP in the years 2014 to 2016. Thus, the specific objectives outlined were: to present basic concepts of the research methodologies; to identify the bibliometric indicators: instruments and methodological approaches of twenty doctoral theses of the PPGCI IBICT and UNESP in the periods of 2014 to 2016; and to apply the simple statistics from the instruments and methodological approaches raised in the programs. The methodology has an exploratory-bibliographic nature, with traits of descriptive research, and qualitativequantitative character, based on the techniques of bibliometric analysis. The results of this research indicate that the most frequent methodological instruments used by IBICT students are interview techniques, semi-structured interview and questionnaire application in the analyzed theses and UNESP techniques are diversified. As for the methodological approaches, exploratory research predominated. Based on the results, it is concluded that, due to the importance of the research methodology for the elaboration of scientific works and due to the interdisciplinary nature, postgraduate studies in Information Science can be applied to undergraduate students as a basis for the development of new investigations.